An Impairment of Prospective Memory in Mild Alzheimer’s Disease: A Ride in a Virtual Town - Lecouvey, Grégory; Morand, Alexandrine; Gonneaud, Julie; Piolino, Pascale; Orriols, Eric; Pélerin, Alice; Ferreira Da Silva, Laurence; de La Sayette, Vincent; Eustache, Francis; Desgranges, Béatrice (Frontiers in Psychology, 2019)
Objective: Research suggests that prospective memory is impaired from the very early stages of Alzheimer’s disease. We sought to further characterize this impairment in patients with mild Alzheimer’s disease, using a virtual reality task to provide ecological assessment of prospective memory. Method: Fifteen cognitively normal older individuals (76.47 years old ± 4.14, MMSE: 28.80 ± 1.21), and 17 patients with mild Alzheimer’s disease (79.29 years old ± 4.45, MMSE: 22.82 ± 2.83) were asked to recall the prospective and retrospective components of seven intentions in a virtual town task. Six intentions were event-based, where the prospective cue was either highly (three intentions) or weakly (three intentions) associated with the retrospective component. The remaining intention was time-based. All participants completed a neuropsychological assessment of episodic memory, semantic memory and executive functioning. Non-parametric tests were used to compare the two groups on the different intentions types and components. Correlations between cognition and prospective memory scores were then realized to further understand the cognitive correlates of the PM impairment in patients with Alzheimer’s disease. Results: Overall, patients with Alzheimer disease recalled fewer intentions than controls, with the retrospective component and time-based intentions being the most challenging for them. The strength of the association between the prospective and retrospective components, however, had no effect on their performance. Event-based prospective memory impairment, as well as deficit in the recall of prospective component correlated with memory and executive functions performance. Conclusions: Prospective memory is impaired in Alzheimer’s disease. Both automatic and controlled processes of prospective memory retrieval are disturbed. This study also confirms the reliability of virtual reality for assessing complex cognitive functions such as prospective memory.